1999
DOI: 10.1159/000010095
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Alpha Levels in the Serum and Ascites of Patients withAdv anced Epithelial Ovarian Cancer

Abstract: A variety of cytokines have been identified to play a role in ovarian cancer. In this pilot study, we sought to determine whether transforming growth factor-α (TGF-α) was detectable in the serum and ascites of women with advanced stage epithelial ovarian cancer. TGF-α was measured using an enzyme-linked immunosorbent assay and was present in 18 of 25 control sera. Prior to treatment for stage III or IV epithelial ovarian cancer, 18 patients had undetectable serum levels of TGF-α, while 18 had values ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…be elevated in the ascites fluid of patients with stage III/IV ovarian cancer compared to stage I/II(49). Additionally, histological examinations of the epithelial portion of ovarian tumors(50) and characterization of ovarian cancer lines(51) have shown that some ovarian cancer cells produce TGFα, consistent with our findings here.…”
supporting
confidence: 90%
“…be elevated in the ascites fluid of patients with stage III/IV ovarian cancer compared to stage I/II(49). Additionally, histological examinations of the epithelial portion of ovarian tumors(50) and characterization of ovarian cancer lines(51) have shown that some ovarian cancer cells produce TGFα, consistent with our findings here.…”
supporting
confidence: 90%
“…For example, TGFa levels have been shown to be elevated in the ascites fluid of patients with stage III/IV ovarian cancer compared to stage I/II(49). Additionally, histological examinations of the epithelial portion of ovarian tumors(50) and characterization of ovarian cancer lines(51) have shown that some ovarian cancer cells produce TGFα, consistent with our findings here.…”
supporting
confidence: 89%
“…Accumulation of malignant ascites in the peritoneal cavity is common, particularly in women with late-stage EOC. Thus metastasizing EOC cells exist in a milieu rich in inflammatory cells [88] and growth/signalling factors, including VEGF [8991], EGF [11,92], TGFα, TGFβ [93,94] and LPA [23,95], providing ample opportunity for cross-talk between signalling networks. Ascites accumulation also modifies peritoneal mechanobiology, altering the force environment of both metastatic tumour cells and peritoneal mesothelium [96,97].…”
Section: Microenvironmental Activation Of the Wnt Pathwaymentioning
confidence: 99%